2020
DOI: 10.1177/1049732320962759
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Patient Involvement: Patients’ and Health Professionals’ Perspectives on Decision-Making in the Treatment of Advanced Prostate Cancer

Abstract: Research has shown that involving patients in decisions on treatment may have positive effects for patients. However, there are different understandings of what involving patients implies and different attitudes among physicians toward sharing decisions with patients. This study aimed to explore the attitude of patients with advanced prostate cancer to involvement in treatment decisions and physicians’ and nurses’ approach to patient involvement. Moreover, it aimed to explore whether the decision-making change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“… 45 That patients with haematological malignancies, which are characterised by uncertain trajectories, indistinct transitions and prognostic uncertainty 7 46 47 and novel and evolving treatments, may prefer to defer decisions to specialists, whom they trust, is understandable. Our findings resonate with qualitative studies in Germany 48 and Denmark, 49 that combine interviews with extensive observation of consultations with clinicians and patients with cancer, and which show that most of the time physicians made treatment decisions alone, or with colleagues, with little patient involvement. None of our participants recalled clinicians formally eliciting their preferences regarding decision making, as is recommended, 50 51 yet most felt as involved in this process as they wanted to be, through discussions of treatment options, and clinicians taking time to talk and listen to them, address their concerns, answer questions and offer explanations.…”
Section: Discussionsupporting
confidence: 86%
“… 45 That patients with haematological malignancies, which are characterised by uncertain trajectories, indistinct transitions and prognostic uncertainty 7 46 47 and novel and evolving treatments, may prefer to defer decisions to specialists, whom they trust, is understandable. Our findings resonate with qualitative studies in Germany 48 and Denmark, 49 that combine interviews with extensive observation of consultations with clinicians and patients with cancer, and which show that most of the time physicians made treatment decisions alone, or with colleagues, with little patient involvement. None of our participants recalled clinicians formally eliciting their preferences regarding decision making, as is recommended, 50 51 yet most felt as involved in this process as they wanted to be, through discussions of treatment options, and clinicians taking time to talk and listen to them, address their concerns, answer questions and offer explanations.…”
Section: Discussionsupporting
confidence: 86%
“…Of course it is possible that the older adult had no more questions for the physician and simply understood and agreed with the plan of care, but the lack of negotiation can be seen as an attempt to avoid seeming impolite, not wanting to take the time of a busy professional, or not wanting to appear stupid in front of the knowledgeable (Spiers, 1998). Recent research (Lowe et al, 2021) supports the notion that patients see decision-making about treatment plans to be the role of the physician. Whatever the reason for the lack of negotiation observed, there is little evidence that shared decision-making happens with regularity in outpatient settings.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…When deciding on treatment options, not all prostate cancer patients were offered a choice by their clinicians 7 . Another study found that treatment decisions were considered to be part of the physician's role as both healthcare professionals and patients doubted the latter's abilities to participate in decisions 24 . Therefore, treatment information was emphasized and amounted to patient involvement 24 .…”
Section: Introductionmentioning
confidence: 99%
“… 7 Another study found that treatment decisions were considered to be part of the physician's role as both healthcare professionals and patients doubted the latter's abilities to participate in decisions. 24 Therefore, treatment information was emphasized and amounted to patient involvement. 24 Studies on shared decision‐making for malignant melanoma trajectories are scarce, although it has been found that most melanoma patients prefer an active role and that implementing a shared decision‐making approach in clinics increased patient involvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation